Rebuilding Justice: Reimagining Housemaid Protection through the Lens of Human Rights - Yetniwati, Yetniwati; Hartati, Hartati; Zulkarnain, Iskandar; Kunarti, Siti; Fatricia, Raja Sharah (Journal of Indonesian Legal Studies, 2024)
This paper aims to explain and evaluate the safeguarding of housemaids as a human rights issue, the types of legal safeguards available to them, and the establishment of oversight mechanisms governing the interaction between housemaids and their employers. The need for robust protection arises from the current absence of comprehensive legal frameworks in Indonesia to ensure their rights are upheld. In response, a Draft Bill concerning the Protection of Housemaids is under review as part of the 2023 National Legislation Program (Proglenas), and this paper aims to contribute to the legislative process. Using a normative juridical approach, the research finds that protecting housemaids is a critical step in fulfilling human rights, as acts of abuse and physical violence against them are severe violations. Legal safeguards for housemaids encompass preventive measures such as regulating recruitment processes, employment contracts, working hours, rest periods, leave, wages, overtime pay, and participation in health and work accident insurance programs. Additionally, employer-provided housing must meet health and safety standards. A human rights-based approach to managing work conditions is essential for fostering a harmonious relationship between housemaids and employers. Repressive protection includes mechanisms for resolving disputes, both through non-litigation and litigation methods. Effective legal oversight is vital, which can be conducted routinely by labor agencies and supplemented with online supervision tools, such as a complaint application. This application would allow housemaids and employers to submit complaints, integrated with supervisory staff at the labor department. The conclusion emphasizes that the legal protection of housemaids should be firmly rooted in human rights principles to ensure comprehensive and effective safeguards.